2011
DOI: 10.1007/s00277-011-1241-0
|View full text |Cite
|
Sign up to set email alerts
|

Risk of hepatitis B virus (HBV) reactivation in hepatitis B surface antigen negative/hepatitis B core antibody positive patients receiving rituximab-containing combination chemotherapy without routine antiviral prophylaxis

Abstract: The use of rituximab has been associated with increased risk of hepatitis B virus (HBV) reactivation in patients who are hepatitis B surface antigen (HBsAg) negative and antihepatitis B core antibody (anti-HBc) positive. We aim to determine the rate of HBV reactivation in this group of patients who received rituximab-containing combination chemotherapy without concomitant antiviral prophylaxis and to identify potential risk factors for reactivation. Sixty-two HBsAg negative/anti-HBc positive patients with B-ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
71
0
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(75 citation statements)
references
References 14 publications
0
71
0
4
Order By: Relevance
“…In another Asian study only one (2.3%) of 43 DLBCL patients treated with an R-CHOP regimen showed reactivation of HBV replication [73] , for which a remission was obtained with antiviral therapy with no need to discontinue chemotherapy. Koo et al [74] described HBV reactivation in two (3%) of 62 HBsAg-negative/ anti-HBc-positive patients treated with rituximab-based chemotherapy who did not undergo anti-HBV prophylaxis. More recently, the Asia Lymphoma Study Group investigated for HBV reactivation HBsAg-positive patients and HBsAg-negative/HBcAb-positive patients who received rituximab-based chemotherapy; the study was retrospective and performed on 340 patients, with a reactivation rate of 2.4% in subjects with OBI and 27.8% in HBsAg-positive patients [75] .…”
Section: Hematological Diseasesmentioning
confidence: 99%
“…In another Asian study only one (2.3%) of 43 DLBCL patients treated with an R-CHOP regimen showed reactivation of HBV replication [73] , for which a remission was obtained with antiviral therapy with no need to discontinue chemotherapy. Koo et al [74] described HBV reactivation in two (3%) of 62 HBsAg-negative/ anti-HBc-positive patients treated with rituximab-based chemotherapy who did not undergo anti-HBV prophylaxis. More recently, the Asia Lymphoma Study Group investigated for HBV reactivation HBsAg-positive patients and HBsAg-negative/HBcAb-positive patients who received rituximab-based chemotherapy; the study was retrospective and performed on 340 patients, with a reactivation rate of 2.4% in subjects with OBI and 27.8% in HBsAg-positive patients [75] .…”
Section: Hematological Diseasesmentioning
confidence: 99%
“…On the other hand, the prophylactic administration of an antiviral drug before chemotherapy in HBsAg-negative patients with HBcAb and/or HBsAb positivity is not recommended for economic reasons (48). (26,36) Male sex (13,27) Use of anthracyclines (12,36,41) Cancer type: malignant lymphoma (12,36) Use of rituximab (6,7,(32)(33)(34)42) Cancer type: breast cancer (36,37) Cancer type: liver cancer (22,24) High HBV DNA level (36)(37)(38) HBeAg seropositive (12,22,24) High intrahepatic covalently closed circular DNA (cccDNA) (39) Low titer of HBsAb (31,40) Elevated serum ALT level (25) Figure 2. Pattern of hepatitis B viral reactivation in a hepatitis B surface antigen (HBsAg)-negative patient with hepatitis B core antibody (HBcAb) and/or hepatitis B surface antibody (HBsAb) positivity (7).…”
Section: Hbsag-negative Patients With Hbcab And/or Hbsab Positivitymentioning
confidence: 99%
“…The risk appears to be higher in older patients and patients without antibodies to hepatitis B surface antigen (anti-HBs). 13 Anti-HBs titers may decline or even disappear during chemotherapy, and there is some evidence that this is associated with an increased risk of reactivation; however, the data are limited. Patients with detectable HBV DNA are at particularly high risk and should probably receive preemptive antiviral therapy.…”
Section: Management Of Anti-hbc-positive Patientsmentioning
confidence: 99%
“…Other retrospective studies have reported lower rates of reverse seroconversion with rituximab-based chemotherapy, and uncertainty remains regarding the true risk associated with this agent. 13,14 Given the high prevalence of anti-HBc positivity, particularly in HBV-endemic regions, and the increasing use of rituximab for many conditions, clarifying the risk and appropriate management strategy for patients receiving rituximab needs to be a priority.…”
Section: Reverse Seroconversionmentioning
confidence: 99%